Risk factors analysis for catheter-associated urinary tract infection in urology patients: A cross-sectional survey - Khan, Zafar Ahmad; Akhtar, Adnan (Infectious Diseases Journal of Pakistan, 2025)
Background: Urinary tract infection (UTI) is the most prevalent infectious condition in global healthcare facilities. Urinary tract infections are predominantly attributable to catheter insertion. Approximately 40% of infections in healthcare settings are urinary tract infections, with 80% of these cases resulting from catheter insertion. The aim of this paper is to identify and analyze the risk factors associated with catheter-associated urinary tract infections (CAUTI) in urology patients. Material and Methods: A cross-sectional study involving 365 urology patients who needed catheterization was conducted at Bacha Khan Medical College and Mardan Medical Complex. Information on infections, catheterization, clinical features, demography, and antiseptic use was gathered. Significant risk factors were found using regression analysis after patients were categorized according to their CAUTI status. Results: The average age of the participants was 58.2 years, and 57.5% of them were men. The majority (76.2%) had indwelling catheters, mostly for urine retention (34.5%) or post-operative treatment (41.9%). Significant risk factors for CAUTI included diabetes (AOR: 2.36), longer catheter duration (AOR: 1.27), prolonged hospitalization (AOR: 1.18), and lack of antiseptic measures (AOR: 2.09). CAUTI affected 26.8% of patients. Catheter type, age, and gender did not substantially correlate with CAUTI. Conclusion: Prolonged catheter duration, diabetes, prolonged hospitalization, and lack of antiseptic measures are significant risk factors for CAUTI in urology patients. Keywords: Antiseptic measures, Catheter-associated urinary tract infection, Catheter duration, Diabetes, Risk factors, Urology